Komentar Ujaran Kebencian pada Berita Imigran Jerman dalam Facebook - Lessy Ginsena; Erna Triswantini (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
This study discusses how hate speech comments on German immigrant news in social media Facebook. The purpose of the study is to describe hate speech on German immigrant news in social media Facebook and its forms in the comments column on Facebook. The study uses descriptive qualitative research and illocutionary speech act theory analysis. The results showed that the forms of hate speech found were rassismus and fremdenfeindlichkeit, antisemitismus and antimuslimischer rassismus, sexismus, homo and transphobie, and active politick. The most common hate speech found is politic aktive, namely hatred towards the German government and activists who defend minorities. The most common illocutionary acts found were expressive illocutionary acts in the form of satire for the German government, which according to them, prioritized immigrants over German society